Collecting data on end-of-life decision-making: Questionnaire translation, adaptation and validity assessment. (4th March 2022) - Willmott, Lindy; White, Ben; Feeney, Rachel; Chambaere, Kenneth; Yates, Patsy; Mitchell, Geoffrey; Piper, Donella
Abstract : Little is known in Australia about current practice relating to medical end-of-life decisions preceding patient deaths. This study aimed to translate and culturally adapt a European questionnaire on medical end-of-life decisions and end-of-life care to the Australian context, producing a questionnaire to assess current medical practice in Australia and enable comparison with international studies. Following initial research team review, an English translation of the questionnaire was culturally adapted using four waves of cognitive pre-testing interviews with members of the target community: Australian doctors ( n =27) from different specialties, clinical settings and geographical locations. Cognitive interviewing was used to identify potential problems with the translated questionnaire by examining the cognitive processes participants used to answer questions. Two experts in end-of-life research provided feedback on the questionnaire after the third wave of cognitive interviews. Research team review occurred again after the third and fourth waves of cognitive interviews. Interview notes were reviewed, coded and analysed using content analysis. A consensus approach was used to identify necessary adaptations, with all members of the research team endorsing the adaptations. Following cognitive pre-testing, an online version of the questionnaire was piloted with doctors, nurses and health law researchers ( n =13). Improvements to questionnaire wording, flow/routeing and design were identified during the cognitive interviewing and piloting process and implemented. Saturation in terms of face and content validity and acceptability of the questionnaire was achieved after four rounds of cognitive interviews. Participants generally agreed that the adapted questionnaire instructions were easy to follow, the questions were easy to understand, they felt comfortable answering all the questions, and the online questionnaire format was user friendly. The time taken to complete the questionnaire (average 9.2 min) was also acceptable to participants. Cognitive interviewing was a suitable method for identifying and solving challenges with comprehension and applicability of the questionnaire within the Australian context. The final questionnaire was well accepted by doctors and is now being used in a study exploring the incidence and nature of medical end-of-life decisions involving adult patients in one Australian state (Victoria). This questionnaire may be suitable for use or further adaptation in research in other English speaking jurisdictions.